{What sustains the multidrug resistance phenotype beyond ABC efflux transporters? Looking beyond the tip of the iceberg} - Alexa-Stratulat, Teodora; Pešić, Milica; Gašparović, Ana Čipak; Trougakos, Ioannis P.; Riganti, Chiara (Drug Resistance Updates, 2019)
Identification of multidrug (MDR) efflux transporters that belong to the ATP-Binding Cassette (ABC) superfamily, represented an important breakthrough for understanding cancer multidrug resistance (MDR) and its possible overcoming. However, recent data indicate that drug resistant cells have a complex intracellular physiology that involves constant changes in energetic and oxidative-reductive metabolic pathways, as well as in the molecular circuitries connecting mitochondria, endoplasmic reticulum (ER) and lysosomes. The aim of this review is to discuss the key molecular mechanisms of cellular reprogramming that induce and maintain MDR, beyond the presence of MDR efflux transporters. We specifically highlight how cancer cells characterized by high metabolic plasticity – i.e. cells able to shift the energy metabolism between glycolysis and oxidative phosphorylation, to survive both the normoxic and hypoxic conditions, to modify the cytosolic and mitochondrial oxidative-reductive metabolism, are more prone to adapt to exogenous stressors such as anti-cancer drugs and acquire a MDR phenotype. Similarly, we discuss how changes in mitochondria dynamics and mitophagy rates, changes in proteome stability ensuring non-oncogenic proteostatic mechanisms, changes in ubiquitin/proteasome- and autophagy/lysosome-related pathways, promote the cellular survival under stress conditions, along with the acquisition or maintenance of MDR. After dissecting the complex intracellular crosstalk that takes place during the development of MDR, we suggest that mapping the specific adaptation pathways underlying cell survival in response to stress and targeting these pathways with potent pharmacologic agents may be a new approach to enhance therapeutic efficacy against MDR tumors.
Keywords: ATP-binding cassette transporters; Autophagy; Endoplasmic Reticulum; Lysosomes; Mitochondria; Oxidative-reductive metabolism; Proteasome